2015
DOI: 10.1007/s11356-015-4596-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term exposure to low doses of rotenone induces developmental, biochemical, behavioral, and histological changes in fish

Abstract: Rotenone, a natural compound derived from plants of the genera Derris and Lonchocarpus, is used worldwide as a pesticide and piscicide. This study aims to assess short-term toxicity of rotenone to early-life stages of the fish Danio rerio and Poecilia reticulata using a wide and integrative range of biomarkers (developmental, biochemical, behavioral, and histopathological). Moreover, the species sensitivity distribution (SSD) approach was used to compare rotenone acute toxicity to fish species. Toxicity tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 47 publications
4
29
1
4
Order By: Relevance
“…Rotenone is a natural pesticide widely used, besides to have a relatively short environmental half-life and limited bioavailability, there are evidences that even temporary limited exposure of rotenone could lead the effects in human health (Hatcher et al, 2008; Li et al, 2005; Tanner et al, 2011). Moreover, in vivo and in vitro studies have shown rotenone possible developmental neurotoxicity potential (Khera et al, 1982; Spencer and Sing, 1982; Melo et al, 2015; Krug et al, 2013). For this study, we used a range of concentrations based on published in vitro literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rotenone is a natural pesticide widely used, besides to have a relatively short environmental half-life and limited bioavailability, there are evidences that even temporary limited exposure of rotenone could lead the effects in human health (Hatcher et al, 2008; Li et al, 2005; Tanner et al, 2011). Moreover, in vivo and in vitro studies have shown rotenone possible developmental neurotoxicity potential (Khera et al, 1982; Spencer and Sing, 1982; Melo et al, 2015; Krug et al, 2013). For this study, we used a range of concentrations based on published in vitro literature.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with rotenone has previously shown indications that exposure to this pesticide produce effects on rat, chick and fish development (Khera et al, 1982; Spencer and Sing, 1982; Melo et al, 2015; Rao and Chauhan, 2004) as well as in vitro neurogenesis of iPSC-derived dopaminergic neurons (Fang et al, 2016) and neurite outgrowth (Krug et al, 2013). For example, D. rerio embryos exposed to rotenone showed embryotoxic effects, showing cardiac edema; tail deformities; loss of equilibrium; and a general delay characterized by lack of tail detachment, delayed somite formation, yolk sac absorption, and lack of pigmentation (Melo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Wolf et al (2015) a avaliação de congestão e dilatação de sinusóides pode estar relacionada a forma como o peixe foi eutanasiado. Quanto a necrose hepática, esta foi uma alteração encontrada por outros autores em experimentos com exposição de peixes a agrotóxicos, como em tilápias do Nilo alimentadas com 1.45g/L de deltametrina (Kan et al 2012), Heterobranchus bidorsalis expostos a cipermetrina (Olufayo & Alade 2012) e Poecilia reticulata expostos a 250μg/L de rotenona (Melo et al 2015). Segundo Wolf & Wolfe (2005), a necrose é uma resposta claramente patológica do fígado de peixes relacionada às toxinas.…”
Section: Discussionunclassified
“…Segundo Wolf & Wolfe (2005), a necrose é uma resposta claramente patológica do fígado de peixes relacionada às toxinas. Necrose focal pode estar isolada entre o tecido hepático normal ou infiltrado por células inflamató-rias e é uma alteração que pode estar associada a várias condições tóxicas, incluindo pesticidas (Roberts 2012).O fígado geralmente demonstra os efeitos tóxicos após exposição prolongada (Melo et al 2015), o que foi observado nesse experimento, com o aumento da ocorrência de necrose nos animais expostos cronicamente ao tiametoxam.…”
Section: Discussionunclassified